Hábitos de estudio y rendimiento académico en ingresantes a la Facultad de Ciencias Histórico Sociales de la Universidad Nacional de San Agustín de Arequipa, 2023 - Salas Achircana, Teofilo (2025)
Abstract Socioeconomic status, access to educational resources, and quality of teaching play a key role in the differences observed in students' academic performance; however, another important factor is study habits. The aim was to relate study habits and academic performance in new entrants to the Faculty of Historical and Social Sciences of the National University of San Agustín de Arequipa. The study was basic, quantitative, correlational, non-experimental, cross-sectional; 300 students from 3 professional schools of the Faculty of Historical and Social Sciences participated, taking as a criterion the selection of students by quotas (100 students per professional school). Non-parametric statistical tests were used for inferences because the data do not present a normal distribution. It was found that r= .417** and p=.000, observing that there is a statistically significant correlation at a medium level, direct and 99% reliable. Furthermore, participants have difficulties in most cases in their study habits, due to poor planning, the use of inappropriate techniques and little dedication to study, which are fundamental aspects of vocational training, and support programs must be established to strengthen study habits that help improve this situation. Furthermore, when comparing the results according to socio-academic variables of the incoming students, women have better study habits and perform better because their study plan includes appropriate study schedules and techniques.